Clinical management of spinal metastases—The Dutch national guideline. (November 2018) - Bollen, Laurens; Dijkstra, Sander P.D.; Bartels, Ronald H.M.A.; de Graeff, Alexander; Poelma, Davey L.H.; Brouwer, Thea; Algra, Paul R.; Kuijlen, Jos M.A.; Minnema, Monique C.; Nijboer, Claudia; Rolf, Christa; Sluis, Tebbe; et al.
Abstract: This article is a summary of the revised Dutch multidisciplinary evidence-based guideline 'Spinal metastases' (English translation available at:https://www.oncoline.nl/spinal-metastases ) that was published at the end of 2015. This summary provides an easy-to-use overview for physicians to use in their daily practice. Highlights: The Dutch national multidisciplinary guideline on spinal metastases to improve the quality of care. A summary of the guideline providing an easy-to-use overview for physicians to use in their daily practice. Easy-to-use flowcharts for the diagnostic process and therapy selection in patients with spinal metastases.